2008
DOI: 10.1007/s10067-008-0896-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of liver in two rheumatoid arthritis patients with chronic hepatitis B and C treated with TNF-alpha blockade: case reports

Abstract: Tumor necrosis factor (TNF)-alpha antagonists successfully modulate the pathogenesis of rheumatoid arthritis (RA). However, little is known about the effect of TNF-alpha blockade on the histology of chronic viral hepatitis. We describe the cases of two patients with RA, one with concurrent chronic hepatitis B virus and the other with hepatitis C virus infection who, as part of their evaluation, underwent liver biopsies while undergoing treatment with a TNF-alpha antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 7 publications
0
30
0
2
Order By: Relevance
“…Two years later the patient was switched to etanercept for loss of efficacy, and lamivudine prophylaxis was initiated. Since then, HBV DNA has not been detectable (27). A recent review of the literature revealed that all HBsAg carriers receiving a prophylactic lamivudine regimen did not develop active liver disease (49); however, no prospective studies are available on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two years later the patient was switched to etanercept for loss of efficacy, and lamivudine prophylaxis was initiated. Since then, HBV DNA has not been detectable (27). A recent review of the literature revealed that all HBsAg carriers receiving a prophylactic lamivudine regimen did not develop active liver disease (49); however, no prospective studies are available on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study showed 1 case of viral reactivation among 8 HBsAg carriers treated with anti-TNF␣ therapy (24). On the other hand, many cases have been described in which TNF blockade, either in association with lamivudine prophylactic therapy or not, did not lead to HBV reactivation (6,(25)(26)(27)(28)(29)(30), and recently a retrospective study showed no reactivation during anti-TNF␣ therapy (31). The use of lamivudine to prevent HBV reactivation is recommended in HBsAg-positive patients undergoing immunosuppressive therapies, including anti-TNF␣ drugs (4,32), but its use can lead to viral resistance (33).…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical practice, it is necessary to use anti-TNF-a in these patients. Table 1 summarizes the course of nine patients who received etanercept according to our literature search [16,[22][23][24][25][26]. Nine of four patients were women.…”
Section: Discussionmentioning
confidence: 99%
“…[55], без-опасность длительного применения ингибиторов ФНО α у больных с хроническим вирусным гепатитом (гепатит В, С) не изучена. В некоторых наблюдательных исследованиях сообщается об отсутствии увеличения токсичности при ге-патите С (например, нарастании концентрации печеночных функциональных тестов и уровня вируса) при лечении ин-гибиторами ФНО α [57,58], и в одном контролируемом ис-следовании показано уменьшение выраженности симпто-мов гепатита на фоне лечения этанерцептом [59]. При гепа-тите В все три ингибитора ФНО α вызывают нарастание клинических и лабораторных проявлений гепатита [60].…”
Section: гепатобилиарная системаunclassified